A rating model simulation for risk analysis. (14th January 2008) - Falavigna, Greta
This study analyses the situation of a bank that wants to create an Internal Rating System (IRB). A credit institute can decide to simulate rating judgements from an external rating agency, like Standard and Poor's or Moody's or Fitch Rating. This research compares different frameworks of neural networks, hybrid neuro-fuzzy model and logit/probit model, used to simulate the rating of an external agency. Initially, the models are divided into eight rating classes but the mean percentage error is big. Hence, a two-stage hybrid neuro-fuzzy framework is built, in which the model correctly distinguishes the firms into three macroclasses and then, for each macroclass, a hybrid model divides the firms into eight different classes. This two-stage framework provides good results.